Analisis Materi Akidah Akhlak untuk Mengembangkan Aspek Sikap Siswa - Nova Krisnawati; Samsudin Samsudin (https://ejournal.insuriponorogo.ac.id/, 2025)
The development of students' attitudes aligned with Islamic teachings is a fundamental goal of religious education, particularly in the subject of Akidah Akhlak. However, there remains a gap between the theoretical knowledge imparted and its practical application in students’ daily behavior. This study aims to analyze the content of Akidah Akhlak material for Grade VI students in fostering key attitudes such as faith, honesty, empathy, and environmental awareness. This research method uses a literature review approach to collect, analyze, and synthesize various scientific sources that are relevant to the analysis of material on faith and morals and the development of aspects of student attitudes. The Results reveal that while the content is well-structured and aligns with Islamic educational objectives, its implementation is predominantly theoretical, with limited integration of experiential learning and practical activities. Additionally, the utilization of digital technology as a medium for delivering Akidah Akhlak material remains underexplored, despite its potential to engage students in the digital era. This study concludes that the teaching of Akidah Akhlak must move beyond rote learning to adopt interactive, technology-enhanced, and context-based methods to better internalize Islamic values in students' attitudes and behaviors.